Desain Pengendalian Web Tension pada Roll Winder Menggunakan Kendali Optimal LQR - faizal ahmad faizal; Dian Dian Mursyitah; Ewi Ewi Ismaredah; Syukron Syukron Jamil; Sutoyo Sutoyo Sutoyo (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2019)
Web tension is related to controlling tension on the surface of the paper.Performance on the winder unit for the papermaking process requires smooth control, fast response and a minimum steady state error. So it need the right controller for this plant by paying attention to settling time and the desired natural frequency the sheet of paper. One optimal controller that appropriate to applied is Linear Quadratic Regulation (LQR). The results showed the LQR is able to produce optimal performance, where this control works by weighting the optimal Q and R matrices using trial and error methods.  The system response is able to reach a given setpoint of 0.5 N, and is able to minimize overshoot and maintain steady state, where the parameter values obtained are Ess = 0.0025 N, τ = 0.0732 seconds, tr = 0.4 seconds, ts = 0.1595 seconds, td = 0.0586 seconds, Mp = 0.05%, IAE = 0.03298 Keywords: Integral of Absolute Error (IAE), Linear Quadratic Regulator (LQR), Roll winder, Web tension.